Study of the Association between Diabetes Mellitus and Helicobacter pylori Infection - Fariba Keramat (پزشکی بالینی ابن سینا, 2010)
Introduction & Objective: Helicobacter pylori (H. pylori) is a major gastroduodenal pathogen that is etiologically linked with duodenal and gastric diseases. We aimed to determine the prevalence of H. pylori infection in patients with diabetes mellitus (DM), and to assess the association between H. pylori infection and upper gastrointestinal (GI) symptoms in DM. Materials & Methods: In a case-control study from November 2004 to May 2007 in Hamadan a total of 79 DM patients with upper GI symptoms and 84 aged-matched, non- diabetic patients with upper GI symptoms were included. All patients underwent upper GI endoscopy with biopsy specimens being collected from gastric mucosa. H. pylori was evaluated in each patient by rapid urease test and histology. A serum sample was obtained from each subject for evaluation of antibody against H. pylori using a validated ELISA kit. HbA1C was tested for DM patients. Results: The rates of H. pylori infection in the diabetic and non-diabetic patients were 73.4% and 63.1% respectively (non significant). No association was found between H. pylori infection and upper GI symptoms in the both groups (P> 0.05). The serology test for H. pylori was positive in 54.4% of diabetics and 60.7% of controls (p=0.417, non significant). There was significant difference in rapid urease test between DM patients and non- diabetes controls (70.9% versus 45.2%, p=0.001). Conclusion: H. pylori infection appears not to be associated with DM or upper GI symptoms in DM.